The first report of colonic involvement of angioimmunoblastic T-cell lymphoma - İlker Turan and Nazan Özsan and Başak Doğanavşargil and Eren Arslan Davulcu and Hale Bülbül (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Turan İ, Özsan N, Doğanavşargil B, Arslan Davulcu E, Bülbül H. The first report of colonic involvement of angioimmunoblastic T-cell lymphoma. Turk J Gastroenterol 2020; 5: 413-4.